PENGARUH KUALITAS PRODUK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ( Studi Kasus Pada PT.Nusantara Sakti Semarang ) - Muhammad Sahal Farokhi; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2019)
The development of the business world triggered competition in all fields, especially business competition in the atumotive business world. This research was conducted at PT.Nusantara Sakti Semarang. This study aims to determine the effect of Product Quality (X1), Promotions (X2) dan Price (X3) on Purchase Decisions (Y) consumers of PT.Nusantara Sakti Semarang. This type of research uses Explanatory Research with data collection using interviews and data collection tools using questionmaires with a sample of 100 consymer respondents PT.Nusantara Sakti Semarang using Purposive Sampling anda Accidental Sampling. The analysis technique uses validity test, reliability test, simple linear regression, multiplr linear regression, t test and F tes with SPSS 25.0.From the results of the study showed that the quality of the product has an effect on purchasing decisions of 38,1% promotion has an effect on purchasing decisions of 46,1% and the price has an effect on purchasing decision of 66,6% while simultaneously the quality of products, promotions and price influence purchasing decisions 66,6%. This means that the better the quality of the product, promotion and price, the higher the decision to purchase a Honda Beat at PT.Nusantara Sakti Semarang. Price variables on purchasing decisions have a greater effect than product qualitu and promotion variables. Based on the results of the study, the researcher suggested that PT.Nusantara Sakti Semarang especially in Honda Beat products make improvements and control over the quality of their product and also intensify promotion so that consumer purchasing decisions can increase.